Uma proposta de introdução ao cálculo, como facilitador na aprendizagem matemática - Santos, Diwey Monteiro dos (2019)
This research seeks to defend a proposal for the insertion of concepts of Differential and Integral Calculus in High School in such a way as to facilitate mathematical learning. During our research seven meetings were held with the 30 students of the 3◦ year of the Teaching Center Professor Maria luiza Rodrigues de Sousa aiming to offer an introduction to the concepts of Differential and Integral Calculus, through extra classes in the form of minicourse held during the students’ class shift with an hourly charge of 28 hours/distributed classes, seven modules. During the mini-course, students were initially introduced to the basic concepts of Limit, Derivative and Integral, and activities developed by the students were also proposed, which from the exercises presented by the teacher have the ability to formulate concepts and definitions to improve their knowledge and relate the even with your day-to-day. At the end of each module, a questionnaire was applied to assess the development of the participating students, so through these questionnaires it sought to establish the level of growth to be compared, on the students’ conceptions, before and after the mini-course. From the analysis of the result of this experience, we arrived at the conclusions that corroborated the hypotheses made in the course of the work. Among the conclusions, we show that it is perfectly possible to deal with the concepts of Differential and Integral Calculus in High School and that this approach will have the potential to improve the quality of Mathematics teaching in High School itself